2007
DOI: 10.1021/ic061645o
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Structural Characterization, and Electrophosphorescent Properties of Rhenium(I) Complexes Containing Carrier-Transporting Groups

Abstract: Two novel diimine rhenium(I) carbonyl complexes with the formula [Re(CO)(3)(L)Br], where L = 1-(4-5'-phenyl-1,3,4-oxadiazolylbenzyl)-2-pyridinylbenzoimidazole (1) and 1-(4-carbazolylbutyl)-2-pyridinylbenzoimidazole (2), have been successfully synthesized and characterized by elemental analysis, (1)H NMR, and IR spectra. Their electrochemical, photophysical, and electroluminescent behaviors, along with the X-ray crystal structure analysis of 2, are also described. White electrophosphorescent devices were fabric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
51
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(57 citation statements)
references
References 58 publications
5
51
0
1
Order By: Relevance
“…These assignments are confirmed by the absorption spectra of free phen (Fig. 4a) and the results for related systems [24,25]. The energy gap (Fig.…”
Section: Ir and Uv/vis Propertiessupporting
confidence: 76%
“…These assignments are confirmed by the absorption spectra of free phen (Fig. 4a) and the results for related systems [24,25]. The energy gap (Fig.…”
Section: Ir and Uv/vis Propertiessupporting
confidence: 76%
“…[ 156 ] However, few Re (I) complexes were reported to be used in PhOLEDs owing to the disadvantage of the saturation of emission states resulting from triplet-triplet annihilation which leads to low effi ciency at high current density. [157][158][159] The electrophosphorescent performances of Re (I) complexes can be improved through modifi cation of the ligands. For example, the π -conjugation Ir(ppy-NPh 2 ) 2 (acac) 528 10.3 [120] Ir(ppy) 2 (CBDK) 525 [121] Ir(ppi) 2 (acac) 513 13.4 [122] N N Pt C 6 F 5 space of ligands can be extended via the incorporation of a 2-(4-octadecyloxylphenyl)vinyl group into 2,2 â€Č -bipyridine to adjust the molecular orbital energy levels to give red emission.…”
Section: Re (I) Complexesmentioning
confidence: 99%
“…We have found that the treatment of 1,2,5-oxadiazole-3,4-diamine 7a with 1,10-phenanthroline-5,6-dione 6 in refluxing acetic acid for 2 h gave the target product in 92% yield and high purity (Scheme 1). The same procedure has been used for the preparation of [1,2,5]thiadiazolo [3',4':5,6]pyrazino[2,3-f] [1,10]phenanthroline 5b. The solubility of compounds 5 has decreased dramatically from 5a to 5b.…”
Section: Resultsmentioning
confidence: 99%